Sistem Pakar Diagnosa Penyakit Tanaman Jagung Menggunakan Metode Forward Chaining - Rosmeri Maramba; A Sidiq Purnomo (STMIK Budi Darma, 2024)
One type of grain food crop that originated in America is corn. With corn as the main source of carbohydrates and protein, it is developed as one of the raw materials for the food processing industry. Due to the many pests and diseases that attack corn plants, corn production is currently declining. Forward Chaining is one of the method in the system that works by doing a forward search based on known facts and predetermined rules to conclude or get a new fact. Diseases in corn plants can be diagnosed easily, and special knowledge is needed to distinguish the symptoms, characteristics, and drugs of diseases in corn plants. In addition, precise and thorough diagnosis can help farmers and experts in the diagnosis of corn plant disease attack via the internet. It is expected that the development of a professional system for detecting corn plant diseases will help farmers overcome problems and find effective solutions. The test data used as much as 30 data with this forward chaining method resulted in 27 data that were in accordance with the diagnosis results from experts. Which 27 appropriate data results in a system accuracy of 90%.